China’s strong Female voices: Case Study of Dai Qing - Mishra, Swati (Journal of Posthumanism, 2024)
This paper presents the life and work of Dai Qing, an influential Chinese woman who has made significant contributions to the Chinese state and society. Born during the Republican era, she worked as a party cadre in the PRC. Her efforts in environmental protection, women’s welfare, and freedom of speech are noteworthy. She also played a role in China’s development during Mao era and worked extensively in villages as a Red Guard during the Cultural Revolution. Her life struggles through various phases, and her work on different issues provides firsthand information on China’s development and the condition of Chinese women across different periods. During the Cultural Revolution, she demonstrated her dedication as a cadre without complaint, believing in the communist approach to the nation’s development. However, upon realising the shortcomings of the party system, she began voicing her concerns and documenting these issues in her writings. By providing background about Chinese women in different eras within a Confucian-dominated society, this paper explores how Dai Qing forged her path and remained steadfast in her views and opinions. This paper also portrays a new China where women’s voices are not marginalised, and their ideas are valued.